SIFAT FISIKA MEKANIKA PAPAN SEMEN PURUN TIKUS (Eleocharis dulcis) PADA BERBAGAI PENGERAS (The physical and mechanics properties of mouse purun cement board on various hardeners): Renhart Jemi1 , Yusurum Jagau2 , Yanetri Asi Nion2 , Trisna Anggreini2 , Ria Anjalani2 , Dessy Natalia Koroh1 , Endra Cipta3 , Apri Wijaya Putra4 , Krisna Wahyu4 - Journal, Administrator (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACKThe research objective was to determine the properties of physical and mechanics of mousepurun cement board on various hardeners. The cement board was processed with a size of 30 cmx 30 cm x 2 cm, a ratio of 3: 1, a density of 2 g / cm2, purified water content of 15%, hardenerCa(OH)2, CaCl2, MgCl2 with a concentration of 2%. Before making the cement board thehydration temperature test is carried out, then the resulting board is tested for the physicalproperties of the mechanics. And the grave test for 3 months. Data averaged and SD thentabulated and written in graphical form. The results of the study were hydration temperature:31.38-33.50oC, inhibiting factors: 6.94-10.19%, board water content: 13.55% - 15.77%; density:1.07-1.16 g / cm2; MoR: 22.96 - 30.31 kg / cm2, Compressive strength: 0.84 - 3.34%.Conclusion: Mouse purun can be processed into cement board. The good nature of the cementboard is to treat CaCl2 2% hardener.Keywords: Purun, cement board, hardener, hydration and MoR